Tendencies of Crime Rates and Optimization in the Environment of Globalization - Gavelis, Vytautas (Ekonomika, 2002)
Growth of liberal democracy, integration of global economy, transformation of production systems and labour markets, rapid technological renovation, revolution of mass media as well as entrenchment of consumer ideology negatively influence crime rates in underdeveloped countries. Rising social stratification, high rates of unemployment determinate an increase of street crime rates as well as rates of organized crime. Coalescence of political power and financial oligarchy, development of offshore markets determines an expansion of economic crime and corruption while creation of a society of informational technologies augments computer crime. The use of inborn vices of an individual by mass media raise inability of certain parts of society to differentiate actual reality from a virtual one as well as legal acts from crime. While elaborating economic model of crime optimization it is necessary to refer to real total costs. fixed costs as well as variable costs. The point of intersection of curve of total costs with the indifference curve creates preconditions for locate possible dynamics of crime as well as optimal level of crime on a basis of financial capabilities of a given society.